2004
DOI: 10.1196/annals.1318.034
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Surface‐Bound Nucleic Acids: Free and Cell‐Surface‐Bound Nucleic Acids in Blood of Healthy Donors and Breast Cancer Patients

Abstract: Concentrations of extracellular DNA and RNA in the blood of healthy donors and patients with malignant and nonmalignant breast tumors were investigated. Cell-surface-bound extracellular DNA and RNA were detached by PBS-EDTA treatment or mild trypsin treatment of erythrocytes and leukocytes. In healthy donors, almost all extracellular nucleic acids (98%) are bound at the surface of blood cells. In the blood of cancer patients, extracellular nucleic acids were found in plasma and not at the cell surface. In pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 12 publications
1
79
0
3
Order By: Relevance
“…Questions remain as to the origin of extracellular nucleic acids, which can be found as free nucleic acids [67], bound to a cell's surface via proteins with specialized nucleic acid binding properties [68][69][70], complexed with proteolipids [71,72] and within apoptotic bodies [73]. Studies have shown that they (DNA and RNA) can be released spontaneously from cells [74,75].…”
Section: Origin Of Extracellular Nucleic Acidsmentioning
confidence: 99%
“…Questions remain as to the origin of extracellular nucleic acids, which can be found as free nucleic acids [67], bound to a cell's surface via proteins with specialized nucleic acid binding properties [68][69][70], complexed with proteolipids [71,72] and within apoptotic bodies [73]. Studies have shown that they (DNA and RNA) can be released spontaneously from cells [74,75].…”
Section: Origin Of Extracellular Nucleic Acidsmentioning
confidence: 99%
“…The difference between WBCHO and PLCHO concentrations are explained by several mechanisms: intracellular generation of choline in blood cells by intracellularly located phospholipase D and cell activation pathways (3)(4)(5)(6)(7), existence of a choline transport system in blood cells (10 ), and the fact that choline is removed to a certain extent from plasma via cellular uptake by other tissues (11 ). PLCHO is also a significant predictor of cardiac events, and concentrations increase in acute coronary syndromes complicated by acute left-ventricular failure and severe tissue ischemia (2 ), which was not evident in these cases.…”
mentioning
confidence: 99%
“…2) [96]. С использованием этой обработки внДНК, связанная с поверхностью как ядерных, так и безъядерных клеток крови была обнаружена и у здоровых доноров, и у онкологических больных [97,98]. Так, средняя концентрация ДНК, связанной с поверхностью эритроцитов за счет ионных взаимодействий, в крови здоровых мужчин и женщин составила 298 нг и 57 нг, а с поверхностью лейкоцитов -682 нг и 88 нг, соответственно.…”
Section: внеклеточные днк на поверхности форменных элементов кровиunclassified
“…до 20-25 т.п.н. Более того, и на поверхности эритроцитов, и на поверхности лейкоцитов здоровых доноров была обнаружена низкомолекулярная фракция ДНК размером около 500 п.н., связанная с клеточной поверхностью преимущественно за счёт ионных взаимодействий [97].…”
Section: внеклеточные днк на поверхности форменных элементов кровиunclassified